The function of the present participles in Arabic: An Applied study of the first quarter of the Quran - Malek Yahya (دراسات في اللغة العربيّة وآدابها)
Â Â  This is an applied study of the present participle in the first quarter of the Quran . It shows the principles which Scholars follow to describe the function of the present participle , Such as the constraint of pronunciation as wall as Semantic similarity to the simple present dependence condition . The research concludes that present participle tend to function as a genitive at the Syntactic level. More over , There is no phonological or Semantic similarity between these two cases and whatever similarity thay show is functional and is caused by their formal similarity not their semantic similarity. Â